Pengaruh Total Aktiva, Debt Equity Ratio Dan Earning Per Share Terhadap Manajemen Laba - Wellia Novita (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
The purpose of this study is to examine the impact of total asset, Debt to Equity Ratio (DER)and Earning Per Share (EPS) to earning management using PT Adhi Karya (Persero) Tbkfinancial statement (audited) for the year 2007 to 2011. Based on facts, most of financialstatement’s user only concern to earning not to how company generated the earning. Thisstudy use linear regression as data analysis technic. The results show that total asset, Debt toEquity Ratio and earning per share are significantly and positively influence the earningmanagement at PT Adhi Karya (Persero) Tbk.